Testing, modelling and design of high strength concrete-filled high strength steel tube (HCFHST) stub columns under combined compression and bending. (15th August 2021) - Zhong, Yukai; Sun, Yao; Hai Tan, Kang; Zhao, Ou
Highlights: Eccentric compression tests on high strength concrete-filled high strength steel tube (HCFHST) stub columns were conducted. The structural behaviour and resistances of HCFHST stub columns under combined loading were studied. The eccentric compression test results for HCFHST stub columns were discussed. FE models were developed to validate against the test results and then used to conduct parametric studies. The applicability of the existing design codes to HCFHST stub columns under combined loading was evaluated. Abstract: This paper presents comprehensive experimental and numerical investigations into the structural behaviour and resistances of high strength concrete-filled high strength steel tube (HCFHST) stub columns under combined compression and bending. The combined loading tests were conducted on twelve stub column specimens fabricated from S700 high strength steel square hollow section tubes with two cross-section dimensions and concretes with three grades (C40, C80 and C110). The combined loading test setup, procedures and results, including the failure loads, load–mid-height lateral deflection curves and failure modes, were reported in detail. The failure loads and the evolution of the neutral axis of the HCFHST stub column specimens under combined loading were analysed. The development and distribution of the transverse and longitudinal strains of the outer S700 high strength steel tubes were discussed. The experimental programme was followed by a numerical modelling programme, where finite element models were initially developed and validated against the test results and then used to conduct parametric studies to generate further numerical data. The test and numerical data were used to evaluate the applicability of the relevant design rules, as set out in the European code, American specification and Australian/New Zealand standard, to HCFHST stub columns under combined loading. The evaluation results generally indicated that the European code and Australian/New Zealand standard slightly overestimate the failure loads for HCFHST stub columns under combined loading, while the American specification offers accurate, consistent and safe failure load predictions when applied to eccentrically loaded HCFHST stub columns.